2015
DOI: 10.1016/j.jprot.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals on Cyanothece sp. CCY 0110 growth, extracellular polymeric substances (EPS) production, ultrastructure and protein profiles

Abstract: This work shows the holistic effects of different heavy metals on the cells of the highly efficient EPS-producer the cyanobacterium Cyanothece sp. CCY 0110. The growth/survival, EPS production, ultrastructure, protein profiles and stress response were evaluated. The knowledge generated by this study will contribute to the implementation of heavy-metal removal systems based on cyanobacteria EPS or their isolated polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 69 publications
(105 reference statements)
2
37
0
Order By: Relevance
“…As the first tool of microorganisms to adapt to adverse environments, extracellular polymeric substances (EPS) can prevent heavy metal ions from entering the cells of the microorganism [16]. Considering their minimal nutritional requirements, easy cultivation and rapid metal removal kinetics, EPS-producing cyanobacteria can be an advantageous choice than other microorganisms for treatment of metal wastewater [17]. Cyanobacteria, or blue-green algae, are common microorganisms with the capacity of producing a great deal of EPS [18].…”
Section: Introductionmentioning
confidence: 99%
“…As the first tool of microorganisms to adapt to adverse environments, extracellular polymeric substances (EPS) can prevent heavy metal ions from entering the cells of the microorganism [16]. Considering their minimal nutritional requirements, easy cultivation and rapid metal removal kinetics, EPS-producing cyanobacteria can be an advantageous choice than other microorganisms for treatment of metal wastewater [17]. Cyanobacteria, or blue-green algae, are common microorganisms with the capacity of producing a great deal of EPS [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was recently reported that in Cyanothece sp. CCY 0110, the presence of heavy metals significantly affected its protein profile, in particular with regard to the proteins associated with photosynthesis, CO 2 fixation and carbohydrate metabolism, but did not enhance the amount of RPS released by the cells [ 33 ]. Between other possible elicitors, substances, such as glyoxylate, valerate, acetate or EDTA, are also reported [ 3 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Copper is an essential trace metal for microalgae too (Raven et al 1999;Balamurugan and Schaffner 2006;Peers and Price 2006). However, in excess, all metals are deleterious to the cells (Mota et al 2015). Zinc is phytotoxic at 100 μg/g (Mazumdar and Das 2015).…”
Section: Introductionmentioning
confidence: 99%